Attention load regulates the facilitation of audio-visual information on landing perception in badminton - Wang, X.; Ren, P.; Miao, X.; Zhang, X.; Qian, Y.; Chi, L. (Perceptual and Motor Skills, 2023)
Based on the role of the high temporal sensitivity of the auditory modality and the advantage of audio-visual integration in motion perception and anticipation, we investigated the effect of audio-visual information on landing perception in badminton through two experiments; and we explored the regulatory role of attention load. In this study, experienced badminton players were asked to predict the landing position of the shuttle under the conditions of video (visual) or audio-video (audio-visual) presentation. We manipulated flight information or attention load. The results of Experiment 1 showed that, whether the visual information was rich or not, that is, whether or not it contained the early flight trajectory, the addition of auditory information played a promoting role. The results of Experiment 2 showed that attention load regulated the facilitation of multi-modal integration on landing perception. The facilitation of audio-visual information was impaired under high load, meaning that audio-visual integration tended to be guided by attention from top to bottom. The results support the superiority effect of multi-modal integration, suggesting that adding auditory perception training to sports training could significantly improve athletes` performance.